2023
DOI: 10.1002/ejp.2142
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐evoked potentials in clinical practice: A head‐to‐head contrast with laser‐evoked responses

Abstract: BackgroundInnocuous cooling of the skin activates cold‐specific Aδ fibres, and hence, the recording of cold‐evoked potentials (CEPs) may improve the objective assessment of human thermo‐nociceptive function. While the feasibility of CEP recordings in healthy humans has been reported, their reliability and diagnostic use in clinical conditions have not been documented.MethodsHere, we report the results of CEP recordings in 60 consecutive patients with suspected neuropathic pain, compared with laser‐evoked poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, due to the small cohort, it is not possible to conclude mechanistic conclusions about ongoing spontaneous NP from our data and further studies with larger patient cohorts are necessary. Nonetheless, the following considerations can be made: CEPs allow for the examination of specialized, cool-sensitive Aδ- and C-fibers ( 60 62 ) and their central pathways ( 26 , 28 , 30 , 31 ). While the conduction velocity offers insights into the state of the myelin sheaths, changes in the amplitudes can be due to axonal dysfunction or, as shown for nociceptive pathways ( 63 ), sensitization processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the small cohort, it is not possible to conclude mechanistic conclusions about ongoing spontaneous NP from our data and further studies with larger patient cohorts are necessary. Nonetheless, the following considerations can be made: CEPs allow for the examination of specialized, cool-sensitive Aδ- and C-fibers ( 60 62 ) and their central pathways ( 26 , 28 , 30 , 31 ). While the conduction velocity offers insights into the state of the myelin sheaths, changes in the amplitudes can be due to axonal dysfunction or, as shown for nociceptive pathways ( 63 ), sensitization processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Perchet et al reported on CEPs in patients with suspected NP compared to LEPs. They concluded that “for some patients suffering from symptoms limited only to cold, CEPs but not LEPs may allow the diagnosis of thin fiber pathology” ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…This device is capable of delivering rapid cooling or heating up to 300°C/s. This device has been validated in previous reports in both healthy volunteers [67][68][69][70][71] and clinical pain patients [72,73]. At each formal testing visit (sessions 2-5) participants were familiarized with the thermal probe prior to heat pain thresholding.…”
Section: Pain Thresholdingmentioning
confidence: 99%